State-Making and Labor Movements: France and the United States, 1876-1914 - Saglio, Jean (Relations industrielles / Industrial Relations, 2000)
The article reviews the book, "State-Making and Labor Movements: France and the United States, 1876-1914," by Gerald Friedman.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z